Concurrent tobacco use and binge drinking among university students in 30 countries in Africa, Asia, Latin America, and the Caribbean - Peltzer, Karl; Pengpid, Supa (Springer Science+Business Media, 2017)
The aim of this study was to investigate concurrent tobacco use and binge drinking and the co-occurrence risks of each substance among university students in Africa, Asia, Latin America, and the Caribbean. A cross-sectional survey of 24,753 university students, 58.6% women and 41.4% men, mean age of 20.8 years (SD = 2.6) from 30 countries, was conducted in 2013–2015. Five percent of the university students had engaged in concurrent tobacco use and binge drinking, 17.7% in binge drinking only, and 8.0% in current tobacco use only. Overall, among past month tobacco users, 32.1% were frequent binge drinkers, and among binge drinkers, 45.6% were frequent tobacco users. Compared to students who neither smoked nor were binge drinkers, concurrent tobacco users and binge drinkers were more likely to be men (OR = 3.09, CI = 2.55, 3.74), were older (OR = 2.00, CI = 1.56, 2.36), had a wealthier family background (OR = 1.60, CI = 1.30, 1.96), were living in an upper middle or highincome country (OR = 0.27, CI = 0.10, 0.72), used illicit drugs (OR = 3.16, CI = 2.64, 3.83), were gambling (OR = 2.41, CI = 1.91, 3.04), had been in a physical fight (OR = 2.08, CI = 1.67, 2.59), had sustained an injury (OR = 1.25, CI = 1.03, 1.50), and lacked involvement in organized religious activity (OR = 0.40, CI = 0.32, 0.52). Prevention and treatment strategies should better incorporate the comorbidity of tobacco and alcohol use in their intervention programs.
International Journal Mental Health Addiction (2018) 16:164–174 https://doi.org/10.1007/s11469-017-9850-z
Keywords: Concurrent tobacco use; Binge drinking; University students; 30 countries; Alcoholism; Addiction Severity Index